Valuing GM technologies using real options: the case of drought tolerant wheat in Australia. Issue 12 (2nd December 2018) - Wynn, Katherine; Spangenberg, German; Smith, Kevin F.; Wilson, William
ABSTRACT: In this article we seek to estimate the value of a partially-developed crop technology from the perspective of the firm developing the technology. Firms need this value estimation to decide whether their technology will earn a sufficient return in the market to justify investing in it. However, determining the (ex-ante) value of the technology before it is commercialised is challenging as the technology is not yet in the market and hence the demand function has not yet been defined. An alternative valuation method is required. We use risk premiums, Monte Carlo simulation and real options analysis and we demonstrate this combination of valuation tools on wheat that is currently being developed in Australia to be drought tolerant. The results indicate that this drought tolerant wheat variety is likely to be adopted by farmers in most regions and has a pre-commercialisation value that justifies continued investment in its development. We also identified South Australia as a region in which the new variety would not be sufficiently valuable to farmers to see them adopt it and we consider possible explanations for this outcome.